Complex regional pain syndrome (reflex sympathetic dystrophy) after coronary artery bypass graft - An interesting case - Manjunath Premanath (Wolters Kluwer Medknow Publications, 2021)
A 58-year-old male presented himself with swelling, pain, and color change of the left shoulder, arm, and hand of 3 months duration. His problems started a week after he underwent a coronary artery bypass graft for triple-vessel coronary artery disease. The function of the left upper limb was severely restricted. Investigations done to know the cause of his problems were negative. A clinical diagnosis of complex regional pain syndrome was made. Even though this syndrome was observed after myocardial infarction, its occurrence after CABG has been quite rare. This case is presented as CABG is on the rise, and more and more cases may occur which should not be missed.